2020
DOI: 10.1103/physreva.101.031601
|View full text |Cite
|
Sign up to set email alerts
|

Emission of correlated jets from a driven matter-wave soliton in a quasi-one-dimensional geometry

Abstract: The modulation of the interaction between the atoms in a matter-wave soliton in a quasi-onedimensional optical trap triggers an emission of correlated atom jets. We characterize the dependence of jet properties on the frequency, amplitude and length of the modulation, and qualitatively reproduce the trends in the mean-field picture with a one-dimensional time-dependent Gross-Pitaevskii equation simulation. High-order jets are observed for sufficiently long pulses, a double-pulse modulation sequence produces co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…[27,28] We introduce, in the context of mean-field approach, the expectation values of a j≥0 = â j≥0 and b j≥0 = b j≥0 , where their squares represent the number of particles on site j. In the fireworks experiments, [17,[19][20][21][22] the average dc scattering lengths were generally kept small, and in a previous work we have demonstrated that a finite U did not qualitatively change the results, [27] thus we take the limit of U = 0 for simplicity. We begin from the equilibrium at g = 0, which leads to the Heisenberg equations of motion for a j≥0 (taking units where h = 1)…”
Section: Theoretical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…[27,28] We introduce, in the context of mean-field approach, the expectation values of a j≥0 = â j≥0 and b j≥0 = b j≥0 , where their squares represent the number of particles on site j. In the fireworks experiments, [17,[19][20][21][22] the average dc scattering lengths were generally kept small, and in a previous work we have demonstrated that a finite U did not qualitatively change the results, [27] thus we take the limit of U = 0 for simplicity. We begin from the equilibrium at g = 0, which leads to the Heisenberg equations of motion for a j≥0 (taking units where h = 1)…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Such amplification offers stimulating applications in quantum metrology and simulation of highly nonequilibrium systems. Subsequently, a number of experimental and theoretical groups have performed a series of follow-up investigations and revealed various new aspects, [19][20][21][22][23][24][25][26] e.g., the jet substructure in nonuniform and rotating condensates [20] and correlated jets from a driven matter-wave soliton. [22] In particular, semi-infinite and infinite lattice models were introduced to mimic the behaviors of the trapped particles in a transparent way, [27,28] where the time evolution of the atoms in the horizontal plane was simulated by the hopping of particles from the condensate to the "leads" and between neighboring sites, and the spatial expansion was simply limited in one dimension.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic field fluctuations can also result in fluctuations in the trap position, leading to heating of the trapped atoms [7]. In experiments with Bose-Einstein condensates, where a sudden change from a repulsive to an attractive interaction can create matter-wave solitons [8] or a periodic modulation of the interaction can lead to the emission of matter-wave jets [9,10], the precise control over the interaction is required. This translates into the need for precise magnetic field control at the sub-mG level.…”
Section: Introductionmentioning
confidence: 99%
“…A sudden change of the scattering length has been achieved experimentally recently [6]. In atomic BECs, many fascinating nonequilibrium dynamics are involved with tuning interatomic interaction, such as the formation of matter-wave solitons [7][8][9][10], the transformation between different types of vector solitons [11], controlled collapse [12], Faraday patterns [13], collective excitation modes [14,15] and matter-wave jet emission [16][17][18][19].…”
mentioning
confidence: 99%